PENGARUH UMUR BIAKAN CENDAWAN Aspergillus sp. ISOLAT LOKAL PALOLO TERHADAP MORTALITAS Helopeltis spp. (HEMIPTERA : MIRIDAE) - Pasaru, Remalia Bulo; Panggeso, Johanis; Khasanah, Nur (AGROTEKBIS, 2017)
This research aims to determine the effect of the amount of spores in the age difference cultured fungus Aspergillus sp. local isolates palolo on mortality Helopeltis spp. This research    used experimental methods of design are collated in a completely randomized design (CRD), which is testing the amount spores in each respective age culture 3, 5, 7, and 9 days, and the dose of spores in each age culture from isolates local palolo Aspergillus sp. on the death of test insects Helopeltis spp. The research was carried on in the Laboratory of Plant Pests and Diseases, Faculty of Agriculture, University of Tadulako, from May 2015 to July 2015. The results showed that in treatment P4 (age cultures of 9 days) the amount spores is more that 8.748 x 106sel and has effective power better in a deadly test insects Helopeltis spp. compared with the treatment of breeding age 3 days, 5 days, and 7 days. Key Words: Aspergillus sp., Cocoa (Theobromae cacao), Helopeltis spp.